PRE-SERVICE ENGLISH TEACHERS’ PERCEPTIONS OF PRONUNCIATION - Aina Khoirida (Universitas Islam Sumatera Utara (UISU), 2020)
The studies that look at pre-service teachers’ perceptions of the teaching of pronunciation which is still relatively under-researched in the literature. Previous research on pronunciation commonly gave more attention to the designs to conduct the teaching pronunciation in the classroom, like the methods and the materials. In connection to that, this meant it is leading to what should be taught and how in pronunciation L2 class. This study aimed to look at the pre-service English teachers’ perceptions and understanding they are covered about concerning pronunciation teaching. The data for this study was collected through questionnaires with 18 pre-service English teachers from the English Education Department in a public university in Surakarta and interviews with three of them. The findings bring about questions for practice, teachers training, and professional improvement of the participants. The results add to the discussion about the background of the teachers’ knowledge related to pronunciation teaching. The issues raised also underline the need for more research in several areas, especially attitude toward pronunciation.